2-Stage and 3-stage restorative proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis show comparable short- and long-term outcomes - Brunner, Maximilian; Brandl, Martin; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Weber, Klaus (Scientific Reports, 2024)
Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) represents the standard treatment for therapy-refractory, malignant or complicated ulcerative colitis (UC) and can be performed as a 2-stage or 3-stage procedure. This study aimed to compare the short- and long-term outcomes after 2- and 3-stage IPAA in patients with UC in our department. A retrospective analysis of 176 patients with UC who received 2- or 3-stage restorative proctocolectomy with IPAA at our institution from 2001 to 2021 was performed. Outcomes for short-term (morbidity, longer hospital stay, readmission) and long-term (pouch failure and quality of life) parameters were compared between the 2- and 3-stage procedure. Regarding short-term outcomes for all patients, in-hospital morbidity and readmission rates after any surgical stage were observed in 69% and 24%, respectively. Morbidity and readmission did not differ significantly between the 2- and 3-stage procedure in uni- and multivariate analysis. Median length of hospital stay for all stages was 17 days. The 3-stage procedure was identified as an independent factor for longer hospital stay (OR 3.8 (CI 1.3-10.8), p = 0.014). Pouch failure and failure of improved quality of life during long-term follow-up occurred both in 10% of patients, with no significant differences between the 2- and 3-stage procedure in uni- and multivariate analysis. Our data suggest that both the 2- and 3-stage proctocolectomy with IPAA demonstrate favourable and comparable postoperative short- and long-term outcomes, with a high rate of improved quality of life in patients with UC.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Ileal pouch-anal anastomosis; Outcome; Pouch failure; Proctocolectomy; Ulcerative colitis

Antibiotic treatment after appendectomy for acute complicated appendicitis to prevent intrabdominal abscess and wound infections - Laverde, Bruno Leonardo Bancke; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Langenbecks Archives of Surgery, 2024)
Introduction: The purpose of this analysis was to investigate the most appropriate duration of postoperative antibiotic treatment to minimize the incidence of intraabdominal abscesses and wound infections in patients with complicated appendicitis. Materials and methods: In this retrospective study, which included 396 adult patients who underwent appendectomy for complicated appendicitis between January 2010 and December 2020 at the University Hospital Erlangen, patients were classified into two groups based on the duration of their postoperative antibiotic intake: ≤ 3 postoperative days (group 1) vs. ≥ 4 postoperative days (group 2). The incidence of postoperative intraabdominal abscesses and wound infections were compared between the groups. Additionally, multivariate risk factor analysis for the occurrence of intraabdominal abscesses and wound infections was performed. Results: The two groups contained 226 and 170 patients, respectively. The incidence of postoperative intraabdominal abscesses (2% vs. 3%, p = 0.507) and wound infections (3% vs. 6%, p = 0.080) did not differ significantly between the groups. Multivariate analysis revealed that an additional cecum resection (OR 5.5 (95% CI 1.4–21.5), p = 0.014) was an independent risk factor for intraabdominal abscesses. A higher BMI (OR 5.9 (95% CI 1.2–29.2), p = 0.030) and conversion to an open procedure (OR 5.2 (95% CI 1.4–20.0), p = 0.016) were identified as independent risk factors for wound infections. Conclusion: The duration of postoperative antibiotic therapy does not appear to influence the incidence of postoperative intraabdominal abscesses and wound infections. Therefore, short-term postoperative antibiotic treatment should be preferred.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Appendectomy; Complicated appendicitis; Intraabdominal abscess; Postoperative antibiotic therapy; Wound infection

Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Colon Cancer Microbiome Landscaping: Differences in Right- and Left-Sided Colon Cancer and a Tumor Microbiome-Ileal Microbiome Association - Kneis, Barbara; Wirtz, Stefan; Weber, Klaus; Denz, Axel; Gittler, Matthias; Geppert, Carol-Immanuel; Brunner, Maximilian; Krautz, Christian; Siebenhuener, Alexander Reinhard; Schierwagen, Robert; Tyc, Olaf; Agaimy, Abbas; et al. (International Journal of Molecular Sciences, 2023)
In the current era of precision oncology, it is widely acknowledged that CRC is a heterogeneous disease entity. Tumor location (right- or left-sided colon cancer or rectal cancer) is a crucial factor in determining disease progression as well as prognosis and influences disease management. In the last decade, numerous works have reported that the microbiome is an important element of CRC carcinogenesis, progression and therapy response. Owing to the heterogeneous nature of microbiomes, the findings of these studies were inconsistent. The majority of the studies combined colon cancer (CC) and rectal cancer (RC) samples as CRC for analysis. Furthermore, the small intestine, as the major site for immune surveillance in the gut, is understudied compared to the colon. Thus, the CRC heterogeneity puzzle is far from being solved, and more research is necessary for prospective trials that separately investigate CC and RC. Our prospective study aimed to map the colon cancer landscape using 16S rRNA amplicon sequencing in biopsy samples from the terminal ileum, healthy colon tissue, healthy rectal tissue and tumor tissue as well as in preoperative and postoperative stool samples of 41 patients. While fecal samples provide a good approximation of the average gut microbiome composition, mucosal biopsies allow for detecting subtle variations in local microbial communities. In particular, the small bowel microbiome has remained poorly characterized, mainly because of sampling difficulties. Our analysis revealed the following: (i) right- and left-sided colon cancers harbor distinct and diverse microbiomes, (ii) the tumor microbiome leads to a more consistent cancer-defined microbiome between locations and reveals a tumor microbiome-ileal microbiome association, (iii) the stool only partly reflects the microbiome landscape in patients with CC, and (iv) mechanical bowel preparation and perioperative antibiotics together with surgery result in major changes in the stool microbiome, characterized by a significant increase in the abundance of potentially pathogenic bacteria, such as Enterococcus. Collectively, our results provide new and valuable insights into the complex microbiome landscape in patients with colon cancer.
CRIS-Team Scopus Importer:2023-03-10
Keywords: colon cancer; gut microbiome; left-sided colon cancer; microbiome; right-sided colon cancer; tumor microbiome

Cylindric Abdominoperineal Rectum Exstirpation with Partial Vulvar and Vaginal Resection as well as Perineal and Vaginal Defect Reconstruction by a Vertical Rectus Abdominis Myocutaneous (VRAM) Flap - Krautz, Christian; Weber, Klaus; Croner, Roland; Denz, Axel; Maak, Matthias; Horch, Raymund E.; Grützmann, Robert (Zentralblatt für Chirurgie, 2017)
Introduction Patients with low rectal cancer or anal cancer undergoing abdominoperineal excision (APE) benefit from extended surgery and the subsequent avoidance of surgical "waisting" at the level of the puborectalis muscle. The method of cylindrical APE was introduced by T. Holm and led to a reduction of intraoperative perforations and involvement of circumferential resection margins, and subsequently reduced the risk of local recurrence. The use of myocutaneous flaps reduces perineal wound complications, which occur in up to 60% of patients with primary closure of perineal defects, especially following neoadjuvant radiochemotherapy. Flaps obliterate pelvic dead space, recruit well-vascularised tissue into irradiated regions, facilitate wound closure and allow for vaginal and perineal reconstructions. This video shows the technique of extended cylindrical APE with partial vulvar and vaginal resection and subsequent reconstruction of the posterior vaginal wall and the pelvic floor defect by a vertical rectus abdominis myocutaneous (VRAM) flap. Indication Locally advanced anal cancer with infiltration and fistula to the posterior vaginal wall without metastatic spread following neoadjuvant radiochemotherapy. Procedure Extended cylindric APE with partial vulvar and vaginal resection, construction of a descending colostomy with parastomal intraperitoneal onlay mesh augmentation, pelvic reconstruction with a VRAM flap and inlay mesh augmentation of the anterior rectus sheath. Conclusion From the oncological point of view, extralevator APE is superior to standard surgery. The use of myocutaneous flaps improves postoperative wound healing and quality of life.
EVALuna2:15291

Effects of a metabolic optimized fast track concept (MOFA) on bowel function and recovery after surgery in patients undergoing elective colon or liver resection: A randomized controlled trial - Uhlig, Christopher; Rössel, Thomas; Denz, Axel; Seifert, Sven; Koch, Thea; Heller, Axel Rüdiger (BMC Anesthesiology, 2019)
Background: Enhanced recovery after surgery programs (ERAS) using thoracic epidural anesthesia and perioperative patient conditioning with omega-3 fatty acids (n3FA), glucose control (GC) and on-demand fluid therapy, respectively, showed beneficial effects. In the MOFA- study these components were used together in patients undergoing colon or liver surgery. We hypothesized that the use of a perioperative MOFA program improves intestine function represented as time to the first postoperative bowel movement in adult patients compared to standard ERAS. Methods: After BfArM and IRB approval 100 patients were enrolled in this prospective randomized controlled trial. All patients received ERAS therapy (control). In addition, the MOFA group received 0.2 g/kg fish oil (Omegaven®), preoperatively, followed by a 48 h continuous infusion of 0.2 g/kg/d n3FA; and GC was kept below < 8 mmol/L. Pre- and postoperatively energy drinks were administered. Results: As compared to control group the MOFA concept resulted in an earlier onset of flatulence by 14 h (46.6 ± 25.7, 32.0 ± 17.9, p = 0.030, hours, control vs. MOFA, respectively). Effects on onset of bowel movement were not observed (74.5 ± 30.4, 66.4 ± 29.2, p = 0.163, hours, control vs. MOFA, respectively). The disease severity (SAPS II score; p = 0.720) as well as deployment of resources (TISS 28 score, p = 0.709) did not differ between groups. No statistic significant difference between MOFA and control group regarding inflammation, impairment of coagulation, length of hospital stay or incidence of postoperative surgical complications were observed. Conclusions: The MOFA concept did not result in an improvement of intestine function or faster recovery after elective colon or liver surgery compared to standard ERAS therapy. Omega-3 fatty acids showed no impairment of coagulation or improved resolution of inflammation. Further trials in a larger patient collective are needed to investigate potential beneficial effects of omega-3 fatty acids in abdominal surgery. Trial registration: This trial was prospectively registered at the European Union Clinical Trials Register (EuDraCT 2005-004814-33, date: 10-05-2005, https://www.clinicaltrialsregister.eu/ctr-search/search?query=2005-004814-33+).
CRIS-Team Scopus Importer:2019-08-30
Keywords: Abdominal surgery; Colon surgery; ERAS; Liver surgery; Omega-3 fatty acids; Omegaven; Randomized controlled trial; Recovery after surgery

Effects of Positive End-Expiratory Pressure and Spontaneous Breathing Activity on Regional Lung Inflammation in Experimental Acute Respiratory Distress Syndrome - Kiss, Thomas; Bluth, Thomas; Braune, Anja; Huhle, Robert; Denz, Axel; Herzog, Moritz; Herold, Johannes; Vivona, Luigi; Millone, Marco; Bergamaschi, Alice; Andreeff, Michael; Scharffenberg, Martin; et al. (Critical Care Medicine, 2019)
Objectives: To determine the impact of positive end-expiratory pressure during mechanical ventilation with and without spontaneous breathing activity on regional lung inflammation in experimental nonsevere acute respiratory distress syndrome. Design: Laboratory investigation. Setting: University hospital research facility. Subjects: Twenty-four pigs (28.1-58.2 kg). Interventions: In anesthetized animals, intrapleural pressure sensors were placed thoracoscopically in ventral, dorsal, and caudal regions of the left hemithorax. Lung injury was induced with saline lung lavage followed by injurious ventilation in supine position. During airway pressure release ventilation with low tidal volumes, positive end-expiratory pressure was set 4 cm H 2 O above the level to reach a positive transpulmonary pressure in caudal regions at end-expiration (best-positive end-expiratory pressure). Animals were randomly assigned to one of four groups (n = 6/ group; 12 hr): 1) no spontaneous breathing activity and positive end-expiratory pressure = best-positive end-expiratory pressure -4 cm H 2 O, 2) no spontaneous breathing activity and positive end-expiratory pressure = best-positive end-expiratory pressure + 4 cm H 2 O, 3) spontaneous breathing activity and positive endexpiratory pressure = best-positive end-expiratory pressure + 4 cm H 2 O, 4) spontaneous breathing activity and positive endexpiratory pressure = best-positive end-expiratory pressure 4 cm H 2 O. Measurements and Main Results: Global lung inflammation assessed by specific [18F] fluorodeoxyglucose uptake rate (median [25-75% percentiles], min-1) was decreased with higher compared with lower positive end-expiratory pressure both without spontaneous breathing activity (0.029 [0.027-0.030] vs 0.044 [0.041-0.065]; p = 0.004) and with spontaneous breathing activity (0.032 [0.028-0.043] vs 0.057 [0.042-0.075]; p = 0.016). Spontaneous breathing activity did not increase global lung inflammation. Lung inflammation in dorsal regions correlated with transpulmonary driving pressure from spontaneous breathing at lower (r = 0.850; p = 0.032) but not higher positive end-expiratory pressure (r = 0.018; p = 0.972). Higher positive end-expiratory pressure resulted in a more homogeneous distribution of aeration and regional transpulmonary pressures at end-expiration along the ventral-dorsal gradient, as well as a shift of the perfusion center toward dependent zones in the presence of spontaneous breathing activity. Conclusions: In experimental mild-to-moderate acute respiratory distress syndrome, positive end-expiratory pressure levels that stabilize dependent lung regions reduce global lung inflammation during mechanical ventilation, independent from spontaneous breathing activity.
CRIS-Team WoS Importer:2019-06-18

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

High locoregional Control Rates after Radio (chemo) Therapy in anaplastic Thyroid Carcinoma - a monocentric Analysis - Schmied, M.; Semrau, Sabine; Hecht, Markus; Lettmaier, Sebastian; Mantsopoulos, K.; Traxdorf, Maximilian; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of gender on radiosensitivity during radiochemotherapy of advanced rectal cancer - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Büttner-Herold, Maike; Weber, Klaus; Denz, Axel; Grützmann, Robert; Hartmann, Arndt; Geinitz, Hans; Fietkau, Rainer; et al. (Cancers, 2022)
Gender is increasingly recognized as an important factor in medicine, although it has long been neglected in medical research in many areas. We have studied the influence of gender in advanced rectal cancer with a special focus on radiosensitivity. For this purpose, we studied a cohort of 495 men (84.1% ≥ T3, 63.6% N1, 17.6%, M1) and 215 women (84.2% ≥ T3, 56.7% N1, 22.8%, M1) who all suffered from advanced rectal cancer and were treated with radiochemotherapy. The energy deposited, DNA double-strand break (dsb) repair, occurrence of chromosomal aberrations, duration of therapy, tumor regression and tumor-infiltrating lymphocytes, laboratory parameters, quality of life and survival were assessed. The residual DNA dsb damage 24 h after irradiation in lymphocytes was identical in both sexes. Furthermore, chromosomal aberrations accurately reflecting radiosensitivity, were similar in both sexes. There were no gender-dependent differences in tumor regression, tumor-infiltrating lymphocytes and outcome indicating no differences in the radiosensitivity of cancer cells. The irradiated tumor volume in women was slightly lower than in men, related to body weight, no difference was observed. However, when the total energy deposited was calculated and related to the body weight, women were exposed to higher amounts of ionizing radiation. During radiochemotherapy, decreases in blood lymphocyte counts and albumin and several quality-of-life parameters such as nausea and vomiting, loss of appetite, and diarrhea were significantly worse in women. There is no difference in radiation sensitivity between men and women in both normal tissue and tumors. During radiochemotherapy, the quality of life deteriorates more in women than in men. However, women also recover quickly and there are no long-term differences in quality of life.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Blood values; Deposited energy; DNA double-strand breaks; Gender; Quality of life; Radiochemotherapy; Radiosensitivity; Radiosensitivity; Rectal cancer

Influence of Hospital Volume Effects and Minimum Caseload Requirements on Quality of Care in Pancreatic Surgery in Germany - Krautz, Christian; Denz, Axel; Grützmann, Robert; Weber, Georg (Visceral Medicine, 2017)
Numerous international studies have identified hospital volume as significant independent variable of death following pancreatic surgery. Most of these studies were limited to regions of countries or portions of a national population and did not include data on volume-outcome effects in Germany.The Medline database was systematically searched to identify studies that analyzed volume-outcome relationships and effects of minimum caseload requirements on outcomes of pancreatic surgery in Germany.Recent observational studies utilizing German hospital discharge data confirmed that patients undergoing pancreatic surgery in Germany also have better outcomes when treated in facilities with high annual caseloads. Besides a decreased risk of in-hospital mortality, there is also a reduced risk of 1-year mortality in high-volume hospitals. In addition, there is evidence that adherence to already existing minimum caseload requirements reduces morbidity and mortality of pancreatic surgery in Germany. As a result of an insufficient centralization in the recent past, however, a large proportion of hospitals that perform pancreatic surgery still do not meet minimum caseload requirements.Specific measures (i.e. sanctions for failure to achieve minimum volumes) that initiate a sufficient centralization process without threatening patient access to surgical care are needed.
EVALuna2:15293

Influence of interrupted versus continuous suture technique on intestinal anastomotic leakage rate in patients with Crohn’s disease — a propensity score matched analysis - Mittelstädt, Anke; von Löffelholz, Tobias; Weber, Klaus; Denz, Axel; Krautz, Christian; Grützmann, Robert; Weber, Georg; Brunner, Maximilian (International Journal of Colorectal Disease, 2022)
Purpose: Intestinal anastomosis is a crucial step in most intestinal resections, as anastomotic leakage is often associated with severe consequences for affected patients. There are especially two different techniques for hand-sewn intestinal anastomosis: the interrupted suture technique (IST) and the continuous suture technique (CST). This study investigated whether one of these two suture techniques is associated with a lower rate of anastomotic leakage. Methods: A retrospective review of 332 patients with Crohn’s disease who received at least one hand-sewn colonic anastomosis at our institution from 2010 to 2020 was performed. Using propensity score matching 183 patients with IST were compared to 96 patients with CST in regard to the impact of the anastomotic technique on patient outcomes. Results: Overall anastomotic leakage rate was 5%. Leakage rate did not differ between the suture technique groups (IST: 6% vs. CST: 3%, p = 0.393). Multivariate analysis revealed the ASA score as only independent risk factor for anastomotic leakage (OR 5.3 (95% CI = 1.2–23.2), p = 0.026). Suture technique also showed no significant influence on morbidity and the re-surgery rate in multivariate analysis. Conclusion: Our data suggest that the chosen suture technique (interrupted vs. continuous) has no influence on postoperative outcome, especially on anastomotic leakage rate. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Anastomotic leakage; Continuous suture technique; Crohn’s disease; Interrupted suture technique; Intestinal anastomosis

Ökonomische Auswirkung der COVID-19-Pandemie in der Allgemein- und Viszeralchirurgie: Ein Vergleich von Leistungs- und Erlösdaten zweier Kliniken aus Krankenhäusern unterschiedlicher Versorgungsstufen - Binder, Johannes; Brunner, Maximilian; Maak, Matthias; Denz, Axel; Grützmann, Robert; Krautz, Christian; Weber, Georg (Chirurg, 2021)
Background: During the first wave of the coronavirus disease 2019 (COVID-19) pandemic, German hospitals were required to limit the capacity for elective surgery to prevent the healthcare system from general overload. In March 2020, the German government passed the COVID-19 Hospital Relief Act that guaranteed compensation payments for these limitations. In this study the regional impact of this intervention were analyzed. Material and methods: The performance data and revenue figures for the departments of general and visceral surgery of the University Hospital of Erlangen (UKER) and the District Hospital St. Anna Höchstadt/Aisch (KKH) during the period from 1 April to 30 June 2019 were compared with the respective period in 2020. Results: There was a significant decrease in bed occupancy rates and case numbers of inpatient treatment. The latter declined by 20.06% in the UKER and 60.76% in the KKH. Nononcological elective surgery was reduced by 33.04% in the UKER and 60.87% in the KKH. The number of emergency procedures remained unchanged in the UKER, while they decreased by 51.58% in the KKH. The revenues from diagnosis-related groups (DRG) decreased by 22.12% (UKER) and 54% (KKH), respectively. After taking compensation payments and savings from variable material costs into account, the UKER recorded a loss of −3.87%, while there was a positive revenue effect of 6.5% in the KKH. Discussion: The nonselective restriction of elective surgery had a significant impact on patient care and revenue figures at both locations. With respect to the increase of intensive care capacities, such untargeted measures do not appear to be efficient. In addition, the fixed rate of compensation payments led to an unbalanced distribution of the financial aid between the two departments.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Coronavirus; DRG billing data; Hospital Relief Act; Surgery; Treatment quality

Omega suture technique for minimally invasive rectal anastomosis – a video vignette - Brunner, Maximilian; Weber, Klaus; Denz, Axel; Langheinrich, Melanie; Kersting, Stephan; Weber, Georg; Grützmann, Robert; Krautz, Christian (Colorectal Disease, 2023)
CRIS-Team Scopus Importer:2023-05-19

Palliativchirurgie beim kolorektalen Karzinom – welche Faktoren können bei der Wahl des operativen Vorgehens helfen? - Konopke, Ralf; Schubert, Joerg; Stoeltzing, Oliver; Thomas, Tina; Kersting, Stephan; Denz, Axel (Zentralblatt für Chirurgie, 2020)
Background The surgical procedure for patients with colorectal cancer (CRC) in the palliative situation cannot be adequately standardised. The present study was initiated to identify criteria for the decision for resection of the malignancy with or without anastomosis. Patients/Material and Methods In a unicentric retrospective analysis, 103 patients after palliative resection with or without anastomosis due to CRC were examined. Using univariate and logistic regression analysis, the influence of a total of 40 factors on postoperative morbidity and mortality was assessed. Results In 46 cases, resection with primary anastomosis and in 57 cases a discontinuity resection was performed. Postoperative morbidity was 44.7% and mortality 17.5%. After one-stage resection with anastomosis, nicotine abuse (OR 4.2; p = 0.044), hypalbuminaemia (OR 4.0; p = 0.012), ASA score > 2 (OR 3.7; p = 0.030) and liver remodelling/cirrhosis (OR 3.6; p = 0.031) increased the risk for postoperative complications. Hypalbuminaemia (OR 1.8; p = 0.036), cachexia (OR 1.8; p = 0.043), anaemia (OR 1.5; p = 0.038) and known alcohol abuse (OR 1.9; p = 0.023) were identified as independent risk factors for early postoperative mortality. After discontinuity resection, renal failure (OR 2.1; p = 0.042) and cachexia (OR 1.5; p = 0.045) led to a significant increase in the risk of postoperative morbidity, alcohol abuse (OR 1.8; p = 0.041) in mortality. Hypalbuminaemia (OR 2.8; p = 0.019) and an ASA score > 2 (OR 2.6; p = 0.004) after resection and reconstruction increased the risk of major complications according to Clavien-Dindo, while pre-existing renal failure (OR 1.6; p = 0.023) increased the risk after discontinuity resection. In univariate analysis, an ASA score > 2 (p = 0.038) after simultaneous tumour resection and reconstruction, and urgent surgery in both groups with or without primary anastomosis were additionally identified as significant parameters with a negative influence on mortality (p = 0.010 and p = 0.017). Conclusion Palliative resections of colorectal carcinomas have high morbidity and mortality. Especially in cases of pre-existing alcohol abuse and/or urgent indication for surgery, more intensive monitoring should be performed. In the case of anaemia, cachexia, hypalbuminemia and an ASA score > 2, discontinuity resection may be the more appropriate procedure.
CRIS-Team Scopus Importer:2020-12-25
Keywords: colorectal carcinoma; morbidity; mortality; palliative medicine

Predictive factors of early outcome after palliative surgery for colorectal carcinoma - Konopke, Ralf; Schubert, Jörg; Stöltzing, Oliver; Thomas, Tina; Kersting, Stephan; Denz, Axel (Innovative Surgical Science, 2020)
A significant number of patients with colorectal cancer are presented with various conditions requiring surgery in an oncologically palliative setting. We performed this study to identify risk factors for early outcome after surgery to facilitate the decision-making process for therapy in a palliative disease. We performed a retrospective chart review of 142 patients who underwent palliative surgery due to locally advanced, complicated, or advanced metastatic colorectal carcinoma between January 2010 and April 2018 at the "Elbland"Medical Center Riesa. We performed a logistic regression analysis of 43 factors to identify independent predictors for complications and mortality. Surgery included resections with primary anastomosis (n=31; 21.8%) or discontinuous resections with colostomy (n=38; 26.8%), internal bypasses (n=27; 19.0%) and stoma formation only (n=46; 32.4%). The median length of hospitalization was 12 days (2-53 days), in-hospital morbidity was 50.0% and the mortality rate was 18.3%. Independent risk factors of in-hospital morbidity were age (HR: 1.5, p=0.046) and various comorbidities of the patients [obesity (HR: 1.8, p=0.036), renal failure (HR: 1.6, p=0.040), diabetes (HR: 1.6, p=0.032), alcohol abuse (HR: 1.3, p=0.023)] as well as lung metastases (HR: 1.6, p=0.041). Arteriosclerosis (HR: 1.4; p=0.045) and arterial hypertension (HR: 1.4, p=0.042) were independent risk factors for medical complications in multivariate analysis. None of the analyzed factors predicted the surgical morbidity after the palliative procedures. Emergency surgery (HR: 10.2, p=0.019), intestinal obstruction (HR: 9.2, p=0.006) and ascites (HR: 5.0, p=0.034) were multivariate significant parameters of in-hospital mortality. Palliatively treated patients with colorectal cancer undergoing surgery show high rates of morbidity and mortality after surgery. In this retrospective chart review, independent risk factors for morbidity and in-hospital mortality were identified that are similar to patients in curative care. An adequate selection of patients before palliative operation should lead to a better outcome after surgery. Especially in patients with intestinal obstruction and ascites scheduled for emergency surgery, every effort should be made to convey these patients to elective surgery by interventional therapy, such as a stent or minimally invasive stoma formation.
CRIS-Team Scopus Importer:2020-11-20
Keywords: colorectal cancer; metastasis; palliative surgery; palliative treatment; surgery

Radio(chemo)therapy in anaplastic thyroid cancer—high locoregional but low distant control rates—a monocentric analysis of a tertiary referral center - Schmied, Matthias; Lettmaier, Sebastian; Semrau, Sabine; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
Background: Anaplastic thyroid cancer (ATC) is a lethal disease with highly aggressive disease progression. This study analyses the influence of radio(chemo)therapy, R(C)T, on disease control, survival rates and predictors for survival. Patients and methods: A total of 33 patients with ATC, treated at a tertiary referral center between May 2001 and April 2020 were included. Univariate and multivariate analysis were used to investigate correlates of R(C)T and predictors on disease control and survival rates. Results: Median follow-up was 4 months. In UICC stage IVA and IVB median overall survival (OS) was 8 months, median progression-free survival (PFS) was 6 months. Patients with UICC stage IVA and IVB and patients being irradiated with a radiation dose of more than 60 Gy showed increased OS. Of these patients, 3 were alive and free from disease. All of them receiving cisplatin-based radiochemotherapy and a minimum radiation dose of 66 Gy. UICC stage IVC showed a median OS of 2.5 months and a median PFS of 1 month. Only 2 of 16 patients had local failure. Conclusion: Depending on UICC stage, RT with high radiation dose can lead to improved OS or at least higher locoregional control. A limiting factor is the high incidence of distant metastases; therefore modern systemic treatment options should be integrated into multimodal therapy concepts.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Anaplastic thyroid cancer; Chemotherapy; Multimodal treatment; Radiation dose; Radiotherapy

Repeating of local therapy of distant metastases increases overall survival in patients with synchronous metastasized rectal cancer-a monocentric analysis - Haderlein, Marlen; Lettmaier, Sebastian; Langheinrich, Melanie; Schmid, Axel; Semrau, Sabine; Hecht, Markus; Beck, Michael; Schmidt, Daniela; Grützmann, Robert; Fietkau, Rainer; Denz, Axel (International Journal of Colorectal Disease, 2018)
PURPOSE: The aim was to evaluate the outcome of treatment-naive patients with synchronous metastatic rectal cancer after chemotherapy with FOLFOXIRI followed by local therapeutic procedures of all tumor lesions as complete as possible. METHODS: We reviewed data of 30 patients with synchronous distant metastatic rectal cancer who underwent chemotherapy with FOLFOXIRI and subsequent local therapy in our institution. RESULTS: Median follow-up was 28 months (range: 8; 74). Cumulative overall survival (OS) and progression-free survival (PFS) was 93.3, 76.9, 55.6% and 46.2, 29.7, 29.7% after 1, 2, 4 years. Non-response to chemotherapy with FOLFOXIRI was associated with a highly significant decreased OS (p < 0.0001). The consistent use of local ablative procedures led to a statistically significant increase in OS (p < 0.0001), but not in PFS (p = 0.635). Patients with ≤ 4 distant metastases showed a better OS (p = 0.033). CONCLUSIONS: Response to intensified first-line chemotherapy with FOLFOXIRI, treatment of the primary rectal tumor, and repeated thorough local ablative procedures in patients with synchronous metastasized rectal cancer may lead to long-term survival, even in a subset of patients with unresectable disease at initial diagnosis.
EVALuna2:36458

Risk Factors for Conversion from Laparoscopic to Open Appendectomy - Bancke Laverde, Bruno Leonardo; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
(1) Background: Since its introduction in the 1990s, laparoscopic appendectomy has become established over the years and is today considered the standard therapy for acute appendicitis. In some cases, however, a conversion to the open approach is still necessary. The primary aim of this study was to identify risk factors for the need to convert from the laparoscopic to an open approach during appendectomy for acute appendicitis. (2) Methods: A retrospective analysis of 1220 adult patients who underwent laparoscopic appendectomy for acute appendicitis from 2010 to 2020 at the University Hospital Erlangen was performed. Data, including patient demographics and pre-, intra-, and postoperative findings, were collected and compared between patients with and without conversion. (3) Results: The conversion rate in our cohort was 5.5%. A higher preoperative WBC count and CRP (OR 1.9, p = 0.042, and OR 2.3, p = 0.019, respectively), as well as the presence of intraoperative perforation, necrosis or gangrene, perityphlitic abscess and peritonitis (OR 3.2, p = 0.001; OR 2.3, p = 0.023; OR 2.6, p = 0.006 and OR 2.0, p = 0.025, respectively) were identified as independent risk factors for conversion from the laparoscopic to the open approach. Conversion was again independently associated with higher morbidity (OR 2.2, p = 0.043). (4) Conclusion: The laparoscopic approach is feasible and safe in the majority of patients with acute appendicitis. Only increased inflammatory blood markers could be detected as the preoperative risk factors potentially influencing the choice of surgical approach but only with low specificity and sensitivity. For the decision to convert, intraoperative findings are additionally crucial. However, patients with conversion should receive special attention in the postoperative course, as these have an increased risk of developing complications.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acute appendicitis; conversion; laparoscopic approach; morbidity

Risk Factors for Postoperative Major Morbidity, Anastomotic Leakage, Re-Surgery and Mortality in Patients with Colonic Perforation. - Brunner, Maximilian; Gärtner, Lara; Weiß, Andreas; Weber, Klaus; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert (Journal of Clinical Medicine, 2024)
Background/Objectives: This study aimed to determine the risk factors associated with postoperative major morbidity, anastomotic/suture leakage, re-surgery and mortality in patients undergoing emergency surgery for colonic perforation. Methods: A total of 204 adult patients treated surgically for colonic perforation from 2016 to 2021 at the University Hospital Erlangen were included in a retrospective analysis. Patient demographics and pre-, intra- and postoperative parameters were obtained and evaluated among various outcome groups (in-hospital major morbidity, anastomotic/suture leakage, re-surgery and 90-day mortality). Results: Postoperative in-hospital major morbidity, anastomotic/suture leakage, need of re-surgery and 90-day mortality occurred in 45%, 12%, 25% and 12% of the included patients, respectively. Independent risk factors for in-hospital major morbidity were identified and included the presence of any comorbidity, a significantly reduced preoperative general condition, the localization of perforation in the right hemicolon and the need for an intraoperative blood transfusion. The only independent risk factor for anastomotic/suture leakage was the presence of any comorbidity, whereas no independent risk factors for re-surgery were found. An age > 65 years, a significantly reduced preoperative general condition and the need for an intraoperative blood transfusion were independent risk factors for 90-day mortality. Conclusions: Our study identified risk factors impacting postoperative outcomes in patients undergoing emergency surgery for colonic perforation. These patients should receive enhanced postoperative care and may benefit from individualized and targeted therapeutic approaches.
EVALuna2:582568

Risk factors for postoperative morbidity, prolonged length of stay and hospital readmission after appendectomy for acute appendicitis - Laverde, Bruno Leonardo Bancke; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (European Journal of Trauma and Emergency Surgery, 2023)
PurposeThe aim of the present study was to identify risk factors associated with postoperative morbidity and major morbidity, with a prolonged length of hospital stay and with the need of readmission in patients undergoing appendectomy due to acute appendicitis.MethodsWe performed a retrospective analysis of 1638 adult patients who underwent emergency appendectomy for preoperatively suspected acute appendicitis from 2010 to 2020 at the University Hospital Erlangen. Data including patient demographics, pre-, intra-, and postoperative findings were collected and compared between different outcome groups (morbidity, major morbidity, prolonged length of postoperative hospital stay (LOS) and readmission) from those patients with verified acute appendicitis (n = 1570).ResultsRate of negative appendectomies was 4%. In patients with verified acute appendicitis, morbidity, major morbidity and readmission occurred in 6%, 3% and 2%, respectively. Mean LOS was 3.9 days. Independent risk factors for morbidity were higher age, higher preoperative WBC-count and CRP, lower preoperative hemoglobin, longer time to surgery and longer duration of surgery. As independent risk factors for major morbidity could be identified higher age, higher preoperative CRP, lower preoperative hemoglobin and longer time to surgery. Eight parameters were independent risk factors for a prolonged LOS: higher age, higher preoperative WBC-count and CRP, lower preoperative hemoglobin, need for conversion, longer surgery duration, presence of intraoperative complicated appendicitis and of postoperative morbidity. Presence of malignancy and higher preoperative WBC-count were independent risk factors for readmission.ConclusionAmong patients undergoing appendectomy for acute appendicitis, there are relevant risk factors predicting postoperative complications, prolonged hospital stays and readmission. Patients with the presence of the identified risk factors should receive special attention in the postoperative course and may benefit from a more individualized therapy.
CRIS-Team WoS Importer:2023-03-03

Roboterassistierte viszeralchirurgische Eingriffe in Deutschland: Eine Analyse zum aktuellen Stand sowie zu Trends der letzten 5 Jahre anhand von StuDoQ|Robotik-Registerdaten - Brunner, Maximilian; Elgendy, Amr; Denz, Axel; Weber, Georg; Grützmann, Robert; Krautz, Christian (Die Chirurgie, 2023)
Robot-assisted systems have been increasingly used in general surgery for several years. Accordingly, the number of systems installed in Germany has also rapidly increased. While around 100 robot-assisted systems were used in German hospitals in 2018, this figure had already risen to more than 200 by 2022. The aim of this article is to present the current state of development and trends in robotic surgery in Germany. For this purpose, data from the StuDoQ|Robotics register were analyzed. Furthermore, a descriptive analysis of concomitant diagnosis-related groups (DRG) data was carried out via the Federal Statistical Office (Destatis), for a better assessment of the representativeness of the StuDoQ|Robotics register data. In both data sets, the annual number of robot-assisted visceral surgery procedures in Germany steadily increased. Compared to the DRG data, only 3.7% up to a maximum of 36.7% of all robot-assisted procedures performed were documented in the StuDoQ|Robotics register, depending on the type of procedure. Colorectal resections were the most frequent robot-assisted procedures (StuDoQ: 32.5% and 36.7% vs. DRG data: 24.2% and 29.7%) and had, for example, low mortality rates (StuDoQ: 1% and 1% vs. DRG data: 2.3% and 1.3%). Due to the low coverage rates of robot-assisted esophageal, gastric, pancreatic and liver interventions, no valid statements could be derived from the StuDoQ data for these areas. With the current coverage rates, the informative value of the StuDoQ|Robotics register is considerably limited for some types of intervention. In the future, measures should therefore be explored that lead to a significant increase in the coverage rates.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Hospital billing data; Robotic colorectal surgery; Robotic hepato-pancreato-biliary surgery; Robotic surgery of the upper gastrointestinal tract; StuDoQ register

RREB1::MRTFB fusion-positive extra-glossal mesenchymal neoplasms: A series of five cases expanding their anatomic distribution and highlighting significant morphological and phenotypic diversity - Agaimy, Abbas; Din, Nasir Ud; Dermawan, Josephine K.; Haller, Florian; Melzer, Katja; Denz, Axel; Baumhoer, Daniel; Stöhr, Robert; Grützmann, Robert; Antonescu, Cristina R. (Genes Chromosomes & Cancer, 2022)
The RREB1::MRTFB (former RREB1::MKL2) fusion characterizes ectomesenchymal chondromyxoid tumors (EMCMT) of the tongue. Only five molecularly confirmed extra-glossal EMCMT cases have been reported recently; all occurring at head and neck or mediastinal sites. We herein describe five new cases including the first two extracranial/extrathoracic cases. The tumors occurred in three male and two female patients with an age ranging from 18 to 61 years (median, 28). Three tumors were located in the head and neck (jaw, parapharyngeal space, and nasopharyngeal wall) and two in the soft tissue (inguinal and presacral). The tumor size ranged from 3.3 to 20 cm (median, 7). Treatment was surgical without adjuvant treatment in all cases. Two cases were disease-free at 5 and 17 months; other cases were lost to follow-up. Histologically, the soft tissue cases shared a predominant fibromyxoid appearance, but with variable cytoarchitectural pattern (cellular perineurioma-like whorls and storiform pattern in one case and large polygonal granular cells embedded within a chondromyxoid stroma in the other). Two tumors (inguinal and parapharyngeal) showed spindled to ovoid and round cells with a moderately to highly cellular nondescript pattern. One sinonasal tumor closely mimicked nasal chondromesenchymal hamartoma (NCMH). Mitotic activity was low (0-5 mitoses/10 hpfs). Immunohistochemical findings were heterogeneous with variable expression of S100 (2/5), EMA (2/3), CD34 (1/4), desmin (1/4), and GFAP (1/3). Targeted RNA sequencing revealed the same RREB1::MRTFB fusion in all cases, with exon 8 of RREB1 being fused to exon 11 of MRTFB. This study expands the topographic spectrum of RREB1::MRTFB fusion-positive mesenchymal neoplasms, highlighting a significant morphological and phenotypic diversity. Overall, RREB1::MRTFB-rearranged neoplasms seem to fall into two subcategories: tumors with lobulated, chondroid, or myxochondroid epithelioid morphology (Cases 2 and 3) and those with more undifferentiated hypercellular spindle cell phenotype (Cases 1, 4, and 5). Involvement of extracranial/extrathoracic sites and the NCMH-like pattern are novel. The biology of these likely indolent or benign tumors remains to be verified in the future.
CRIS-Team WoS Importer:2022-07-29

Survival outcome following surgical versus non-surgical treatment of colorectal lung metastasis—a retrospective cohort study - Denz, Axel; Hahn, Veronika; Weber, Klaus; Weber, Georg; Grützmann, Robert; Krautz, Christian; Brunner, Maximilian (Langenbecks Archives of Surgery, 2024)
Purpose: The optimal management of colorectal lung metastases (CRLM) is still controversial. The aim of this study was to compare surgical and non-surgical treatment for CRLM regarding the prognostic outcome. Methods: This retrospective single-center cohort study included 418 patients, who were treated from January 2000 to December 2018 at a German University Hospital due to their colorectal carcinoma and had synchronous or metachronous lung metastases. Patients were stratified according the treatment of the CRLM into two groups: surgical resection of CRLM versus no surgical resection of CRLM. The survival from the time of diagnosis of lung metastasis was compared between the groups. Results: Two- and 5-year overall survival (OS) from the time of diagnosis of lung metastasis was 78.2% and 54.6%, respectively, in our cohort. Patients undergoing pulmonary metastasectomy showed a significantly better 2- and 5-year survival compared to patients with non-surgical treatment (2-year OS: 98.1% vs. 67.9%; 5-year OS: 81.2% vs. 28.8%; p < 0.001). Multivariate Cox regression revealed the surgical treatment (HR 4.51 (95% CI = 2.33–8.75, p < 0.001) and the absence of other metastases (HR 1.79 (95% CI = 1.05–3.04), p = 0.032) as independent prognostic factors in patients with CRLM. Conclusion: Our data suggest that patients with CRLM, who qualify for surgery, benefit from surgical treatment. Randomized controlled trials are needed to confirm our findings. Clinical trial registry number: The work has been retrospectively registrated at the German Clinical Trial Registry (DRKS00032938).
CRIS-Team Scopus Importer:2024-04-26
Keywords: Colorectal carcinoma; Lung metastases; Non-surgical treatment; Outcome; Overall survival; Surgical resection

The G Protein-Coupled Receptor RAI3 Is an Independent Prognostic Factor for Pancreatic Cancer Survival and Regulates Proliferation via STAT3 Phosphorylation - Jahny, Elisabeth; Yang, Hai; Liu, Bin; Jahnke, Beatrix; Lademann, Franziska; Knoesel, Thomas; Ruemmele, Petra; Grützmann, Robert; Aust, Daniela; Pilarsky, Christian; Denz, Axel (PLoS ONE, 2017)
Pancreatic Ductal Adenocarcinoma (PDAC) is one of the deadliest tumors worldwide. Understanding the function of gene expression alterations is a prerequisite for developing new strategies in diagnostic and therapy. GPRC5A (RAI3), coding for a seven transmembrane G protein-coupled receptor is known to be overexpressed in pancreatic cancer and might be an interesting candidate for therapeutic intervention. Expression levels of RAI3 were compared using a tissue microarray of 435 resected patients with pancreatic cancer as well as 209 samples from chronic pancreatitis (CP), intra-ductal papillary mucinous neoplasm (IPMN) and normal pancreatic tissue. To elucidate the function of RAI3 overexpression, siRNA based knock-down was used and transfected cells were analyzed using proliferation and migration assays. Pancreatic cancer patients showed a statistically significant overexpression of RAI3 in comparison to normal and chronic pancreatitis tissue. Especially the loss of apical RAI3 expression represents an independent prognostic parameter for overall survival of patients with pancreatic cancer. Suppression of GPRC5a results in decreased cell growth, proliferation and migration in pancreatic cancer cell lines via a STAT3 modulated pathway, independent from ERK activation.
EVALuna2:6846

The role of intraoperative swab during appendectomy in patients with uncomplicated and complicated appendicitis - Bancke Laverde, Bruno Leonardo; Maak, Matthias; Langheinrich, Melanie; Kersting, Stephan; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (International Journal of Colorectal Disease, 2023)
Introduction: Bacteria play an important role not only in pathogenesis of appendicitis but also in the postoperative course of patients. However, the usefulness of an intraoperative swab during appendectomy is controversial. The primary aim of this study was to investigate the impact of intraoperative swab during appendectomy on the postoperative outcome in patients with uncomplicated and complicated appendicitis. Methods: A retrospective analysis was conducted on a consecutive series of 1570 adult patients who underwent appendectomy for acute appendicitis at the University Hospital Erlangen between 2010 and 2020. Data regarding the intraoperative swab were collected and analyzed for the entire cohort as well as for patients with uncomplicated and complicated appendicitis. Results: An intraoperative swab was taken in 29% of the cohort. The bacterial isolation rate in the obtained intraoperative swabs was 51%, with a significantly higher rate observed in patients with complicated appendicitis compared to those with uncomplicated appendicitis (79% vs. 35%, p < 0.001). The presence of a positive swab was significantly associated with worse postoperative outcomes, including higher morbidity, increased need for re-surgery, and longer hospital stay, when compared to patients without a swab or with a negative swab. A positive swab was an independent risk factor for postoperative morbidity (OR 9.9 (95% CI 1.2–81.9), p = 0.034) and the need for adjustment of postoperative antibiotic therapy (OR 8.8 (95% CI 1.1–72.5), p = 0.043). However, a positive swab resulted in postoperative antibiotic therapy adjustment in only 8% of the patients with bacterial isolation in the swab. Conclusion: The analysis of swab samples obtained during appendectomy for acute appendicitis can help identify patients at a higher risk of a worse postoperative outcome. However, the frequency of antibiotic regime changes based on the swab analysis is low.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Appendectomy; Bacterial isolation; Complicated appendicitis; Intraoperative swab; Uncomplicated appendicitis

The use of single-stapling techniques reduces anastomotic complications in minimal-invasive rectal surgery - Brunner, Maximilian; Zu'bi, Alaa; Weber, Klaus; Denz, Axel; Langheinrich, Melanie; Kersting, Stephan; Grützmann, Robert; Krautz, Christian; Weber, Georg (International Journal of Colorectal Disease, 2022)
Background Leakage of rectal anastomoses is one of the most important and feared complications in colorectal surgery. Apart from patient-specific risk factors, technical aspects may influence the occurrence of anastomotic complications. This study investigated whether using single-stapling techniques (SST) instead of the double-stapling technique (DST) for minimal-invasive rectal anastomosis is associated with a lower rate of anastomotic complications. Methods A retrospective review of 272 patients who received a minimally invasive stapled rectal anastomosis (3-16 cm from the anal verge) at our institution from 2015 to 2020 was performed. In 131 patients, rectal anastomosis was created by SST (SST group), while 141 patients received a rectal anastomosis with crossing stapler lines (DST group). The impact of the anastomotic technique on patient outcomes was determined by uni- and multivariate analyses. Results Overall anastomotic leakage rate was 6%. Patients with SST anastomoses had a lower leakage rate than patients with DST anastomoses (3% vs. 9% in the DST group, p = 0.045). The rate of anastomotic stenosis was lower in the SST group than in the DST group (1% vs. 6%, p = 0.037). Overall morbidity and mortality did not differ between the two groups. Multivariate analysis showed that single-stapling techniques significantly reduce the risk of anastomotic leakage (OR 3.5 [1.0-11.5], p = 0.043). Conclusion The use of SST for rectal anastomosis may help to reduce anastomotic complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team WoS Importer:2022-07-01

Transverse Incision for Pancreatoduodenectomy Reduces Wound Complications: A Single-Center Analysis of 399 Patients - Junker, Stefanie; Jacobsen, Anne; Merkel, Susanne; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
Background: Even if the minimally invasive approach is advancing in pancreatic surgery, the open approach is still the standard for a pancreatoduodenectomy. There are two types of incisions used: the midline incision (MI) and transverse incision (TI). The aim of this study was to compare these two incision types, especially regarding wound complications. Methods: A retrospective review of 399 patients who underwent a pancreatoduodenectomy at the University Hospital Erlangen between 2012 and 2021 was performed. A total of 169 patients with MIs were compared with 230 patients with TIs, with a focus on postoperative fascial dehiscence, postoperative superficial surgical site infection (SSSI) and the occurrence of incisional hernias during follow-up. Results: Postoperative fascial dehiscence, postoperative SSSI and incisional hernias occurred in 3%, 8% and 5% of patients, respectively. Postoperative SSSI and incisional hernias were significantly less frequent in the TI group (SSI: 5% vs. 12%, p = 0.024; incisional hernia: 2% vs. 8%, p = 0.041). A multivariate analysis confirmed the TI type as an independent protective factor for the occurrence of SSSI and incisional hernias (HR 0.45 (95% CI = 0.20–0.99), p = 0.046 and HR 0.18 (95% CI = 0.04–0.92), p = 0.039, respectively). Conclusion: Our data suggest that the transverse incision for pancreatoduodenectomy is associated with reduced wound complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2023-05-12
Keywords: fascial dehiscence; incisional hernia; midline incision; pancreatoduodenectomy; surgical site infection; transverse incision

Treatment and Prognosis of the Oldest Old with Colorectal Cancer - Denz, Axel; Kohl, Valerie; Weber, Klaus; Langheinrich, Melanie; Schellerer, Vera; Merkel, Susanne; Grützmann, Robert (Zentralblatt für Chirurgie, 2018)
INTRODUCTION: The demographic trend will lead to an increase of elderly persons in Germany in the future. The population is becoming smaller and older because of the deficiency in childbirths. This results in demographic ageing of the population in Germany. Studies addressing patients ≥ 85 years, the oldest old, are becoming more and more important. MATERIALS AND METHODS: The prospectively collected data of 141 patients ≥ 85 years with colorectal carcinoma treated between 1995 and 2014 were analysed retrospectively. Treatment, complications and prognosis were compared with a historical group of patients ≥ 85 years treated previously between 1978 and 1994 (n = 57) and with a less old group of patients 75 - 84 years old treated between 1995 and 2014 (n = 726). RESULTS: The cohort consisted of 64 men and 77 women. 88 patients had colon carcinoma, 53 patients rectal carcinoma. 127 patients were treated with tumour resection; 112 were classified as R0. Compared with the historical cohort (1978 - 1994), the number of patients increased, and more patients were given tumour resection (74 vs. 90%, p = 0.003) and fewer patients had synchronous distant metastases (28 vs. 14%, p = 0.015). The 5-year locoregional recurrence rate after curative resection decreased from 11.5 to 1.4% (p = 0.027). Comparison with the younger age group (75 - 84 years) revealed more women (55 vs. 42.3%, p = 0.007), more emergencies (22 vs. 9.8%, p < 0.001) and less frequent neoadjuvant treatment (11 vs. 3%, p = 0.003). Morbidity (41 vs. 31.2%, p = 0.032) and mortality (16 vs. 5%, p < 0.001) were higher in the oldest old. After curative resection and exclusion of postoperative deaths, overall survival (2-year rate 66.4%, 5-year rate 32.9%) was found to be worse than for the less old group, whereas cancer-related survival (2-year rate 93.1%, 5-year rate 86.7%) was similar. CONCLUSION: The number of oldest old patients ≥ 85 years with colorectal carcinoma will further increase. These patients have a higher risk of postoperative complications. After recovering from the surgery cancer-related survival is not worse than for less old patients.
EVALuna2:210714

Treatment of locoregional recurrent colon cancer - Handtrack, Claudia; Weber, Klaus; Merkel, Susanne; Grützmann, Robert; Denz, Axel (Coloproctology, 2022)
The local recurrence rate of colon cancer could be markedly reduced after complete mesocolic excision (CME) criteria were implemented in oncological surgery. Risk factors for local recurrence include incomplete resection as well as the site of the primary tumor and locally or lymph node advanced tumors (pT4/pN2). Further risk factors are emergency operations and postoperative complications, particularly anastomotic leakage. The outcome of local recurrent colon cancer is decisively influenced by the resectability. In cases of a curative R0 resection, possibly including neoadjuvant therapy or multivisceral resections, a 5-year survival rate of over 50% can be achieved.
CRIS-Team WoS Importer:2022-05-27
Keywords: Colorectal cancer; Local recurrence; R0 resection; Staging; Prognosis

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment